Inclusive Early Childhood Education for Children with Special Needs: Challenges and Strategies - Said Ashlan (Pt. Anagata Sembagi Education, 2025)
This study examines the challenges and strategies of implementing inclusive early childhood education for children with special needs through a systematic literature review of 31 academic sources. The synthesis shows that inclusion in early childhood settings remains hindered by insufficient teacher preparedness, rigid standardized curricula, limited multidisciplinary support, poor peer acceptance, parental misalignment, cultural stigma, and inadequate classroom infrastructure. However, the findings also highlight that successful inclusion emerges when learning environments apply differentiated instruction, teacher professional development, collaborative intervention planning, structured social inclusion design, and strong leadership commitment supported by family and community partnerships. Sustainable inclusion requires an educational ecosystem in which pedagogy, institutional support, parental involvement, community values, and resource management function cohesively to ensure equitable participation and positive developmental outcomes. This review provides a holistic strategic foundation to guide early childhood institutions in creating resilient and inclusive learning environments for children with special needs